Model building of doctoral candidates' innovative ability tendency test based on gray target contribution theory. Issue 1 (4th February 2019) - Sun, Caiyun; Shi, Li
Abstract : Purpose: The purpose of this paper is to evaluate doctoral candidates' innovative ability tendency. Design/methodology/approach: This study uses the theory of gray target contribution to analyze the influence degree of doctoral candidates' individual personality factor toward their innovative ability and calculate gray impact quantitative values. Findings: Based on the theory of contribution degree of gray target, a nine-factor model of innovative personality of doctoral candidates is built. IP=f (B, H, G, Q1, Q2, A, I, F, O), (therein: B – intelligence, H – social boldness, G – perseverance, Q1 – experimental, Q2 – independence, A – gregariousness, I – sensibility, F – excitability, O – anxiety). Practical implications: This study based on gray target contribution theory builds nine-factor doctoral candidates' innovative personality model to test the innovative ability tendency of doctoral candidates, which makes cultivating units, mentors and doctoral candidates to know their innovative ability tendency well, perfecting their own knowledge structure in time, effectively improving their innovative ability. The system can also be applied to the work of doctoral candidates as a reference tool to evaluate the innovative ability of applicants. Originality/value: This study quantitatively evaluates the influence of doctoral candidates' personality index on the tendency of doctoral candidates' innovative ability.